PENERAPAN METODE DISAGREGAT DALAM PENYUSUNAN JADWAL INDUK PRODUKSI PADA PABRIK KOPI CENDERAWASIH NABIRE - Hendra Pasu Parningotan Simanjuntak (Jurnal FATEKSA : Jurnal Teknologi dan Rekayasa, 2017)
The purpose of research is to achieved is proposed schedule planning company production that will help control production and suplies. Research methods that used is descriptive qualitatif and quantitaif analysis, while data collection with the methods obswrvation, interview, and documentation. Based on the master scedule whose production has result from disagregate by using the method, can be calculated cost loss due to the advantages and disadvantages of the product and cost saving good stressed master schedule production or by applying the master schedule production for each type of product. Of the is indicated that by applying the master schedule production, the company capable of experiencing cost saving as much 98,08% of total loss prior to master scheduling production.